Asset Pricing with Heterogeneous Consumers - Constantinides, George M.; Duffie, Darrell (Journal of Political Economy, 1996)
Empirical difficulties encountered by representative-consumer models are resolved in an economy with heterogeneity in the form of uninsurable, persistent, and heteroscedastic labor income shocks. Given the joint process of arbitrage-free labor prices, dividends, and aggregate income satisfying a certain joint restriction, it is shown that this process is supported in the equilibrium of an economy with judiciously modeled income heterogeneity. The Euler equations of consumption in a representative-agent economy are replaced by a set of Euler equations that depend not only on the per capita consumption growth but also on the cross-sectional variance of the individual consumers' consumption growth. Copyright 1996 by University of Chicago Press.